2019
DOI: 10.35690/978-2-7592-2784-6
|View full text |Cite
|
Sign up to set email alerts
|

La transformation des grains

Abstract: Centre technique de coopération agricole et rurale (CTA) est une institution internationale conjointe des États du Groupe ACP (Afrique, Caraïbes, Pacifique) et de l'Union européenne (UE). Il intervient dans le cadre des Accords de Cotonou et est financé par l'UE. Pour plus d'information sur le CTA, visitez : www.cta.int CTA,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The heat released from wood or charcoal fire is unbearable for processors. This finding is consistent with Cruz et al (2019) who reported that lack of equipment that is accessible and adapted to processor needs limit their business opportunities.…”
Section: Sellers' Constraintssupporting
confidence: 91%
See 1 more Smart Citation
“…The heat released from wood or charcoal fire is unbearable for processors. This finding is consistent with Cruz et al (2019) who reported that lack of equipment that is accessible and adapted to processor needs limit their business opportunities.…”
Section: Sellers' Constraintssupporting
confidence: 91%
“…This could partially solve the supply challenges faced by traditional processor-retailers throughout the year. The processing of cowpea into dry granules is another way to preserve cowpea and reduce post-harvest loses due to pest infestation (Cruz et al, 2019). Improving storage and packaging can minimize cowpea grain losses due to pests and increase income (Baributsa et al, 2013).…”
Section: Policy Opportunitiesmentioning
confidence: 99%
“…We can therefore correlate the disappearance of certain flocculates from the end-of-cooking corn solution with the nutrition of a few mice that would have stayed there. In this sense, Cruz and al [63] highlights the strong attraction of corn to mice.…”
Section: The Behavior Of the Different Fluids During Resting Sieving ...mentioning
confidence: 96%
“…Rice has some outer envelopes from the flower. These envelopes, called husks, are made up of the glumella and glumes and are not intimately linked to the grain as the pericarp can be, but they improve its protection as in the case of paddy rice (Cruz, .& al. 2020).…”
Section: Plant Materials Generating Agricultural Wastementioning
confidence: 99%